Antibacterial Action of Nanoparticles by Lethal Stretching of Bacterial Cell Membranes. Issue 52 (12th November 2020) - Linklater, Denver P.; Baulin, Vladimir A.; Le Guével, Xavier; Fleury, Jean‐Baptiste; Hanssen, Eric; Nguyen, The Hong Phong; Juodkazis, Saulius; Bryant, Gary; Crawford, Russell J.; Stoodley, Paul; Ivanova, Elena P.
Abstract: It is commonly accepted that nanoparticles (NPs) can kill bacteria; however, the mechanism of antimicrobial action remains obscure for large NPs that cannot translocate the bacterial cell wall. It is demonstrated that the increase in membrane tension caused by the adsorption of NPs is responsible for mechanical deformation, leading to cell rupture and death. A biophysical model of the NP–membrane interactions is presented which suggests that adsorbed NPs cause membrane stretching and squeezing. This general phenomenon is demonstrated experimentally using both model membranes and Pseudomonas aeruginosa and Staphylococcus aureus, representing Gram‐positive and Gram‐negative bacteria. Hydrophilic and hydrophobic quasi‐spherical and star‐shaped gold (Au)NPs are synthesized to explore the antibacterial mechanism of non‐translocating AuNPs. Direct observation of nanoparticle‐induced membrane tension and squeezing is demonstrated using a custom‐designed microfluidic device, which relieves contraction of the model membrane surface area and eventual lipid bilayer collapse. Quasi‐spherical nanoparticles exhibit a greater bactericidal action due to a higher interactive affinity, resulting in greater membrane stretching and rupturing, corroborating the theoretical model. Electron microscopy techniques are used to characterize the NP–bacterial‐membrane interactions. This combination of experimental and theoretical results confirm the proposed mechanism of membrane‐tension‐induced (mechanical) killing of bacterial cells by non‐translocating NPs. Abstract : The mechanism of antimicrobial action for nanoparticles that are unable to translocate across the bacterial cell wall remains obscure. In this work, it is demonstrated that the increase of membrane tension provoked by the adsorption of nanoparticles is responsible for mechanical deformation of the membrane, which leads to bacterial cell rupture and death.